Agent Zero (An Agent Zero Spy Thriller-Book #1) - Jack, Mars (Lukeman Literary, 2019)
"You will not sleep until you are finished with AGENT ZERO. The author did a superb job creating a set of characters who are fully developed and very much enjoyable. The description of the action scenes transport us into a reality that is almost like sitting in a movie theater with surround sound and 3D (it would make an incredible Hollywood movie). I can hardly wait for the sequel." --Roberto Mattos, Books and Movie Reviews In this much-anticipated debut of an epic spy thriller series by #1 bestseller Jack Mars, readers are taken on an action thriller across Europe as presumed-CIA operative Kent Steele, hunted by terrorists, by the CIA, and by his own identity, must solve the mystery of who is after him, of the terrorists' pending target-and of the beautiful woman he keeps seeing in his mind. Kent Steele, 38, a brilliant professor of European History at Columbia University, lives a quiet life in a New York suburb with his two teenage daughters. All that changes when late one night he gets a knock on his door and is abducted by three terrorists-and finds himself flown across the ocean to be interrogated in a basement in Paris. They are convinced that Kent is the most lethal spy the CIA has ever known. He is convinced they have the wrong man. Do they? With a conspiracy around him, adversaries as smart as he is, and an assassin on his tail, the wild game of cat and mouse leads Kent on a perilous road-one that may lead back to Langley-and to a shocking discovery of his own identity. AGENT ZERO is an espionage thriller that will keep you turning pages late into the night. "One of the best thrillers I have read this year." --Books and Movie Reviews (re Any Means Necessary ) Also available is Jack Mars' #1 bestselling LUKE STONE THRILLER series (7 books), which begins with Any Means Necessary (Book #1), a free download with over 800 five star reviews!
Keywords: Dobrodružství, napětí, thrillery